Hidrólise controlada das proteínas do leite de vaca com proteases imobilizadas para redução da alergenicidade - Lopes, Laiane Antunes (Universidade Federal de São Carlos, 2020)
Allergy to cow's milk is clinically an abnormal reaction to cow's milk proteins regulated by immunological mechanisms and which affects mainly children. The partial hydrolysis of these proteins, catalyzed by proteases, offers an efficient way to eliminate, or at least reduce, the allergenic content of milk without significantly affecting its physicochemical and sensory properties. The use of free (soluble) proteases requires thermal inactivation of the enzyme at the end of the reaction, in addition to adding a contaminating molecule to the product. The use of immobilized proteases allows easy separation between enzyme and product and reuse of the catalyst. Multipoint immobilization can also lead to an important increase in the stability of the biocatalyst. In this work, Novo-Pro® D (NPD) and Alcalase® (ALC) proteases were immobilized on 6% agarose support activated with glyoxyl groups (AgGly) and the derivatives obtained were applied to the hydrolysis of cow's milk proteins to reduce allergenic factors in milk. The study of NPD immobilization in AgGly was done, initially, using casein (large molecular weight) and N-benzoyl-L-tyrosine ethyl ester (BTEE, low molecular weight) as substrates. The best results, immobilization yield (YI) of 90%, recovered activity (RA) of 92% (measuring the BTEE hydrolysis) were obtained with immobilization time of 24 h, at 20 ºC and pH 10.0. This derivative was about 20 times more stable than the dialyzed soluble protease, at 50 ºC and pH 6.5, and allowed to achieve a higher degree of hydrolysis (GH) of the casein (26g/L) (40%) than that reached with soluble NPD (34%), under the same reaction conditions. In addition, the derivative could be reused for at least ten batches of 2 hours of reaction. Different strategies were also tested to increase NPD stabilization in AgGly: chemical amination of the enzyme surface before immobilization on AgGly; coating the AgGly derivative with polyethyleneimine (PEI); and partial modification of the glyoxyl groups of the support with carboxylic groups, using glycine to be fixed on the support, and subsequent immobilization and coating with PEI. However, none of these strategies led to greater stabilization than that achieved with the traditional immobilization. Immobilization on chitosan-glutaraldehyde support also did not lead to better results than those already obtained with AgGly. Thus, it followed with the traditional AgGly-NPD derivative and this was compared with the enzyme ALC immobilized on AgGly (AgGly-ALC). The immobilization parameters of ALC and NPD enzymes (dialyzed and non-dialyzed) on AgGly, YI, RA and stability, presented similar values, obtained under the same immobilization conditions. The activities recovered from the derivatives of ALC and NPD were lower when measured with casein hydrolysis, which suggests the presence of a steric impediment in the hydrolysis of this large substrate. In the protein hydrolysis, the higher the degree of hydrolysis (DH), the lower the peptides obtained. However, increasing the degree of hydrolysis to values greater than 5% has also been shown to lead to visible changes in the product. Both derivatives (AgGly-NPD and AgGly-ALC) allowed to obtain approximately 70% of peptides with sizes smaller than 12.4 kDa, for a hydrolysis degree of 5%, suggesting that the main allergenic proteins may have already been sufficiently reduced with this conversion. In the case of soluble protease, in addition to the known disadvantages compared to immobilized protease, there is still difficulty in controlling the final GH, due to the need for inactivating by heating. Regarding the sensory analysis of the hydrolysates obtained, the hydrolysates with 5% DH, obtained with immobilized proteases, showed only small changes in the physicochemical properties of milk, with AgGly-ALC leading to sensory characteristics closer to whole milk than AgGly-NPD. In order to reduce the expected bitter taste that appears in hydrolysis with the generation of hydrophobic peptides in the product, the additions of 5 or 10% of α-cyclodextrin (α-CD) in the hydrolysate with AgGly-ALC were tested, with no reduction in the bitter taste, which suggests that the peptides generated in the hydrolysis of milk did not suit to the cavity of the α-CD molecule. In vivo tests showed that the DH of milk proteins of 5%, with the catalysts AgGly-NPD and AgGly-ALC, allowed to reduce the induction of allergenicity to the milk proteins compared to the in vivo model evaluated, which was not observed with hydrolysates with soluble proteases, which reached higher DH. With the soluble enzyme, although a higher mass percentage of peptides less than 6.5 kDa was obtained, the heating of the milk until the enzyme inactivation (from 50 °C to 90 °C) may have led to the exposure of hidden epitopes or to the appearance of new epitopes with protein denaturation, which induced a greater allergic response of these hydrolysates compared to those hydrolyzed with AgGly-NPD and AgGly-NPD.
Controlled hydrolysis of cow's milk proteins with immobilized proteases to reduce allergenicity
Keywords: Imobilização e estabilização enzimática; Endoproteases; Agarose-glioxil; Hidrólise de proteínas; Alergia ao leite de vaca; Enzyme immobilization and stabilization; Endoproteases; Agarose-glyoxyl; Protein hydrolysis; Cow's milk allergy; ENGENHARIAS::ENGENHARIA QUIMICA